Feasibility Analysis and Implementation Strategy of Multi-Lane Free Flow on the Kayuagung–Palembang–Betung Toll Road - Winanti, Lisa Ayu; Fitriani, Heni; Agustien, Melawaty (Fakultas Teknik Universitas Tanjungpura, 2025)
Traffic congestion at toll gates, caused by long queues of vehicles, remains a significant operational challenge for toll road management in Indonesia. Although the electronic toll collection (E-Toll) system has reduced cash-based transactions, vehicle stops during card tapping continue to limit toll gate capacity during peak traffic. This condition underscores the need for a more efficient toll-collection system. This study aims to evaluate the technical and operational feasibility of implementing the Multi-Lane Free Flow (MLFF) system at the Keramasan–Kayuagung Toll Gate on the Trans-Sumatra Toll Road. Primary data were obtained through direct observation of service time and expert interviews, while secondary data included traffic volume, queue length, and traffic growth rates from relevant agencies. Technical analysis was conducted using queueing system models and time-series traffic forecasting. The results indicate an average service time of 8.381 seconds per vehicle, with an average queue length of 5–7 cars and a service utilization rate of 0.7635 under existing E-Toll operations. Traffic projections indicate that optimal technical conditions for MLFF implementation are expected to be achieved by 2043; however, accelerated implementation by 2034 is feasible through improvements in regulation, infrastructure readiness, and user awareness.